Implementasi Flipbook dalam Pembelajaran CAD untuk Meningkatkan Pemahaman Teknik Assembly Siswa - Marcel Bima Alifiansyah; Muhammad Khumaedi; Khoirul Huda (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Learning assembly techniques in Computer-Aided Design (CAD) subjects in Vocational High Schools (SMK) requires media that supports interactive visualization to facilitate understanding of complex technical concepts. The limitations of conventional media in bridging this need encourages innovation in the use of learning technology. This study aims to analyze the effectiveness of flipbook-based media in improving students' understanding of assembly engineering material. The method used was a quasi-experimental with a two-group pretest-posttest design, involving 40 eleventh-grade students of Mechanical Engineering at SMK Negeri 5 Semarang. The experimental group used flipbooks as a learning medium, while the control group received conventional learning. The results showed a significant increase in the experimental group based on posttest scores (p < 0.05) and an N-Gain value of 64.15%, compared to the control group, which only achieved 43.27%. Thus, flipbooks proved effective in improving students' understanding of assembly engineering material in a more flexible, engaging, and contextual way.